2009
DOI: 10.1111/j.1745-459x.2009.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Strains on Sensory Quality of Pu‐erh Tea in an Improved Pile‐fermentation Process

Abstract: The aim of this study was to evaluate the sensory quality differences between microbe-inoculated and noninoculated tea infusions. Fifteen strains isolate from samples of the 15-year Ta-Huang-In and 25-year Ta-Hon-In of Pu-erh tea were inoculated into the tea leaves and then an improved pile-fermentation process under 60-70% relative humidity at 37C for 42 days was commenced. The results showed that there were significant effects on tea infusion mustiness, floral aroma, caramelness, sweetness, grassiness, fulln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…More than 90% superoxide radical ðO 2 À Þ scavenging activity was observed after 5 d of fermentation for most of the BECMHFs. Among them, S. platensis (S) demonstrated the highest scavenging activity during fermentation, which might have been due to a rich total phenolic content (15.8 AE 0.9 mg/ g) in S. platensis (S) (48,49). S. platensis (S) is rich in proteins, vitamins, essential amino acids, minerals, and essential fatty acids, such as g-linolenic acid (GLA), and is already produced commercially and sold as a food supplement in health food stores worldwide (50).…”
Section: Superoxide Scavenging Activitymentioning
confidence: 99%
“…More than 90% superoxide radical ðO 2 À Þ scavenging activity was observed after 5 d of fermentation for most of the BECMHFs. Among them, S. platensis (S) demonstrated the highest scavenging activity during fermentation, which might have been due to a rich total phenolic content (15.8 AE 0.9 mg/ g) in S. platensis (S) (48,49). S. platensis (S) is rich in proteins, vitamins, essential amino acids, minerals, and essential fatty acids, such as g-linolenic acid (GLA), and is already produced commercially and sold as a food supplement in health food stores worldwide (50).…”
Section: Superoxide Scavenging Activitymentioning
confidence: 99%
“…Furthermore, Chen et al . have demonstrated that microbe‐inoculation has significant effects on the floral, caramel, musty, sweety and grassy notes of tea infusion; Bhattacharyya et al . have found that the grassy smell is transformed into floral smell during the fermentation of black tea .…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [18] also investigated green tea samples from a different point of view. They compared different technologies (microbe-inoculated and noninoculated) of tea fermentation.…”
Section: Introductionmentioning
confidence: 97%